Islamic Bathroom: A Recommendation of Bathroom Layout Design with Islamic Values - Novi Rahmadhani; M Irfan M P Hamid (Talenta Publisher, 2018)
A bathroom is a room that cannot be separated from humans’ daily lives and there are activities performed inside of it. Today’s bathroom usually is designed in the universal style, even though there is no human with the same background nor the same religion. Every religion has its own rules and should be applied by its followers in every aspect of their lives, especially in Islam. There are two guidelines which have the explanation of the bathroom etiquette, Al Quran and Hadits. For the Muslim users, the synchronization between bathroom etiquette and the design of the bathroom is an effort of the observance to Allah SWT. Therefore, this writing is an attempt to give a reminder and also a recommendation of bathroom design layouts based on the rules of Islamic bathroom etiquette. The methodology of this research is to describe all of the bathroom etiquettes in Al-Quran and Hadits and make the concept of the bathroom design layouts based on what is permitted and forbidden.